“Turn on” fluorescence sensors sensitive to volatile organic solvents/plasticizers -perspective and challenges - Kalisz, Justyna; Maksymiuk, Krzysztof; Michalska, Agata; Stelmach, Emilia (Frontiers in Chemistry, 2025)
Organic liquids immiscible with water, such as volatile organic compounds (VOCs) and plasticizers are widespread harmful environmental pollutants, which have long been considered a risk factor for chronic diseases in humans. VOCs or plasticizers in the outdoor environment largely originate from industrial manufacturing, combustion and leakage of transportation fuels, and biological metabolism. Consequently, in order to protect the environment and human health, there is an urgent need for point-of-need sensors for VOCs as well as plasticizer detection. Fluorimetric sensors are emerging attractive tool for monitoring concentration changes of these analytes in environmental samples, that can reduce need for advanced, instrumental methodologies. Various fluorescence-based strategies have already been demonstrated, with turn-on fluorescence approaches being particularly promising. These strategies are based on the interaction of fluorometric dyes or conjugated polymers embedded in polymeric matrices with the target analytes. The proposed approaches show great potential for real-time monitoring of hazardous pollutants in environmental applications, offering cost-efficient, simple, and portable alternatives to conventional analytical techniques. However, it is worth emphasizing that despite the great variety of research topics, the current state of knowledge does not exhaust this field, and many challenges still remain to be overcome.